Analisis Peran Mediator dalam Pelaksanaan Mediasi Perkara Sengketa Ekonomi Syariah ditinjau dari Perma Nomor 1 Tahun 2016 Tentang Mediasi (Mediasi di Pengadilan Agama Batam Kelas 1 A Tahun 2022) - Fauza Andika; Aris Bintania; Muhammad Arif Hudaya; M. Arbisora Angkat (Advances in Humanities and Contemporary Studies, 2024)
In Article 17 Paragraph (1) PERMA Number 1 of 2016 concerning Mediation Procedures in Court it is stated that on the appointed trial day and attended by the parties, the case examiner judge requires the parties to take mediation. The objectives of this research are: To find out the role of the mediator in carrying out the mediation of sharia economic dispute cases at the Batam Class 1 A Religious Court in 2022; To find out and analyze the suitability between the role of the mediator based on PERMA Number 1 of 2016 concerning Mediation Procedures in Courts with practice in the Batam Class 1 A Religious Court. This research is a normative legal research using a statutory approach. The results of the study show that: (1) The role of the mediator in the Batam Religious Court Class 1 A starts from the pre-mediation stage to the mediation process stage; (2) The role of the mediator in the Batam Class 1 A Religious Court has not been fully implemented in accordance with the provisions of PERMA Number 1 of 2016 concerning Mediation Procedures in Courts, this is because there are still several things that have not been carried out by the mediator in the Batam Class 1 A Religious Court, such as: ( 1) optimizing and extending the mediation period; (2) fill out the mediation schedule form; (3) taking inventory of problems and scheduling discussions based on priority scale.